The Role of Student Organizations in the Disruptive Current Cycle - Yohanes Paulus Luciany; Vina Karina Putri; Hariz Rohman Nurtsalits; Muhammad Faadhil Az Zahraan (Tarbiyah Departement collaboration with AMCA, 2023)
There are various kinds of Student Organizations (Ormawa) in every tertiary institution. One of the organizations that researchers will discuss is the Islamic Student Association (HMI). HMI is the oldest student organization in Indonesia. Therefore, HMI must contribute to the nation's next generation, especially in the conditions of an all-sophisticated era or an era of disruption, where knowledge is a basic need. The purpose of this study is to explain the role of student organizations in the Disruptive Current cycle. The research method used is qualitative. Primary data comes from observation, interviews and documentation. The results of the research reveal the role of student organizations as institutions that help raise a generation of professionals. HMI Komisariat Fitrah takes on the role of The Second University. With the Changemaker Hub pattern, it can respond to today's challenges and give birth to a generation of professional intellectuals.